The shadow cabinet - Johnson, Maureen, 1973- (2015)
"Rory, Callum and Boo are still reeling from a series of tragic events, while new dangers lurk around the city from Jane and her nefarious organization"--
Keywords: Boarding schools -- Fiction; Schools -- Fiction; Murder -- Fiction; Ghosts -- Fiction; Boarding schools -- Fiction; Schools -- Fiction; Murder -- Fiction; London (England) -- Fiction; England -- Fiction; London (England) -- Fiction; England -- Fiction; Young adult fiction